2015
DOI: 10.1111/bjh.13441
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of interim FDG‐PET in Hodgkin lymphoma: systematic review and meta‐analysis

Abstract: SummaryThis study aimed to systematically review and meta-analyse the value of interim 18 F-fluoro-2-deoxy-D-glucose positron emission tomography (FDG-PET) in predicting treatment failure in Hodgkin lymphoma. MEDLINE was systematically searched for original studies that used standardized international criteria for interim FDG-PET interpretation. Included studies were methodologically assessed. Summary receiver operating characteristic (sROC) analysis was performed, and pooled sensitivity and specificity were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 36 publications
1
31
0
1
Order By: Relevance
“…The fact that patients with fPET 1 had a significantly worse treatment outcome (P 5 0.03) than did those with dPET 1 and nPET 1 could depend on a possible protective effect of patients with a dPET 1 , as witnessed by the younger age (36.5 vs. 41.8, P 5 0.002), and on the adverse prognostic meaning of a stage IV disease (26). However, when all the known clinical, biologic, and imaging variables were considered, the only strong significant predictive factor associated with a poor PFS in multivariate analysis was positive interim PET/ CT (P , 0.0001), in agreement with the large literature data (26,27). The good interobserver agreement in PET reporting points toward feasibility in clinical practice of these simple rules for BMI detection.…”
Section: Discussionsupporting
confidence: 81%
“…The fact that patients with fPET 1 had a significantly worse treatment outcome (P 5 0.03) than did those with dPET 1 and nPET 1 could depend on a possible protective effect of patients with a dPET 1 , as witnessed by the younger age (36.5 vs. 41.8, P 5 0.002), and on the adverse prognostic meaning of a stage IV disease (26). However, when all the known clinical, biologic, and imaging variables were considered, the only strong significant predictive factor associated with a poor PFS in multivariate analysis was positive interim PET/ CT (P , 0.0001), in agreement with the large literature data (26,27). The good interobserver agreement in PET reporting points toward feasibility in clinical practice of these simple rules for BMI detection.…”
Section: Discussionsupporting
confidence: 81%
“…The metaanalysis lent credence to interim PET by demonstrating pooled sensitivity and specificity values of 0.81 and 0.97, indicating accuracy comparable to that of end-of-treatment imaging (10). A more recent metaanalysis of 10 studies with 1,389 patients reported slightly lower pooled sensitivity and specificity values of 0.71 and 0.90, respectively (11).…”
Section: Interim Response Assessment In Hlmentioning
confidence: 69%
“…2 This meta-analysis showed mixed results among studies, including the subgroup of patients with advanced-stage HL. 2 In particular, studies reporting that a positive interim FDG-PET in advanced-stage HL resulted in low PFS were methodologically flawed, because these studies did not use histopathology or did not report whether histopathology was used to confirm residual disease and instead determined disease relapse by means of follow-up imaging studies. 3,4 Considering the high false-positive rate of follow-up FDG-PET, 5,6 the prognostic value of a positive interim FDG-PET result was likely thoroughly overestimated.…”
mentioning
confidence: 93%
“…[2][3][4] The fact that only 60 patients were PET2 positive and the finding that 58 patients in the PET2-negative group experienced disease relapse indicate that at least approximately half of patients who might have benefited from treatment intensification had negative PET2 results. Note that the volume of FDG-active lymphomatous tissue decreases rapidly after treatment initiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation